Effects of a High‐Probability Request Sequence on Visual Orienting and Instructional Accuracy in a Young Child With Autism. - Sarokoff, Randi A.; Mahoney, Megan A.; El‐Roy, Daphna; DeTiberiis, Jilian Planer (Behavioral Interventions, 2026)
This study evaluated the effects of a high‐probability (high‐p) request sequence on visual orienting to the instructor and response accuracy during discrete trial teaching (DTT) for a 3.5‐year‐old child with autism spectrum disorder (ASD). High‐p sequences involve presenting several simple, high‐likelihood responses prior to a task less likely to be completed (low‐probability; low‐p task). Although high‐p procedures have demonstrated effectiveness in increasing compliance, few studies have examined their effects on observing responses or instructional accuracy. Using an alternating treatments design, we compared visual orienting (defined as eyes open and gaze directed toward the instructor's face for at least 1 s within 5 s prior to SD delivery) and response accuracy across conditions with and without a high‐p sequence. The high‐p condition was associated with consistently higher levels of visual orienting (M = 85%) compared to the low‐p condition (M = 36%), with minimal data overlap. Response accuracy was higher in the high‐p condition (M = 72%) relative to the low‐p condition (M = 57%), although overlap and variability were observed. These findings provide preliminary evidence that high‐p sequences may increase observing responses that support instructional readiness. Limitations related to the identification and measurement of high‐p instructions are discussed.